2017
DOI: 10.1007/s13238-017-0403-9
|View full text |Cite
|
Sign up to set email alerts
|

Shielding of the geomagnetic field reduces hydrogen peroxide production in human neuroblastoma cell and inhibits the activity of CuZn superoxide dismutase

Abstract: Accumulative evidence has shown the adverse effects of a geomagnetic field shielded condition, so called a hypomagnetic field (HMF), on the metabolic processes and oxidative stress in animals and cells. However, the underlying mechanism remains unclear. In this study, we evaluate the role of HMF on the regulation of cellular reactive oxygen species (ROS) in human neuroblastoma SH-SY5Y cells. We found that HMF exposure led to ROS decrease, and that restoring the decrease by additional H2O2 rescued the HMF-enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 40 publications
1
36
0
1
Order By: Relevance
“…Martino and Castello [] also verified that HMF stress suppressed intracellular hydrogen peroxide production, which has been correlated with superoxide dismutase (SOD) activity. Zhang et al [] confirmed that HMF reduces hydrogen peroxide production in human neuroblastoma cells and inhibits the activity of CuZn superoxide dismutase. Therefore, HMF can be considered a stress factor that induces oxidative stress and affects the production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…Martino and Castello [] also verified that HMF stress suppressed intracellular hydrogen peroxide production, which has been correlated with superoxide dismutase (SOD) activity. Zhang et al [] confirmed that HMF reduces hydrogen peroxide production in human neuroblastoma cells and inhibits the activity of CuZn superoxide dismutase. Therefore, HMF can be considered a stress factor that induces oxidative stress and affects the production of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a HMF can significantly suppress Arabidopsis flowering in light [14]. Because of the HMF as a key environmental factor when long-term and longdistance space mission in outer space, and also in some magnetic shielding conditions on the ground,the biological effect of the HMF should be seriously considered [73]. Some studies on the mechanisms underlying the biological effects of a HMF have been carried out [6].…”
Section: The Hyperfine Coupling Mechanism Of Biological Effects On a Hmfmentioning
confidence: 99%
“…In Ouyang and Li [7] the author and his partner gave the point: Equation 1 may be one quantum mechanism of biological effects on a HMF. Ambient alternating fields always exist [73,74] can they influence the biological effects on a HMF ? The author thinks ambient alternating fields can influence the biological effects on a HMF just like on GMF as discussed in part 2.That is to say Equation 2 may be one possible quantum mechanism of the biological effects of a HMF when considering ambient alternating fields.…”
Section: The Hyperfine Coupling Mechanism Of Biological Effects On a Hmfmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) 自由基途径: 动物地磁导航的感光受体 自由基感磁模型认为外界磁场的变化会调控细胞内 的自由基电子自旋状态, 影响不同能级自由基产物 的数量, 例如隐花色素Cry感磁过程 [59,98] , 而体外研 究发现细胞经亚磁场处理后, 通常会引起胞内活性 氧自由基(ROS)的变化. 不同的细胞类型反应不同, 肿瘤细胞系表现胞内ROS水平的下降 [99,100] , 而原代 培养的小鼠肌肉细胞内ROS水平上升 [101] , ROS的变 化破坏了细胞正常的氧化还原平衡, 从而可能引起 与其相关的一些反应. 例如ROS过多可能引起线粒 体细胞膜的损伤, 细胞凋亡等 [102] .…”
Section: 神经细胞是高等动物神经系统的结构和功能单位unclassified